Using Aerial Photogrammetry to Assess Stock-Wide Marine Turtle Nesting Distribution, Abundance and Cumulative Exposure to Industrial Activity - Sabrina Fossette; Graham Loewenthal; Lauren R. Peel; Anna Vitenbergs; Melanie A. Hamel; Corrine Douglas; Anton D. Tucker; Florian Mayer; Scott D. Whiting (Remote Sensing, 2021)
The lack of accurate distribution maps and reliable abundance estimates for marine species can limit the ability of managers to design scale-appropriate management measures for a stock or population. Here, we tested the utility of aerial photogrammetry for conducting large-scale surveys of nesting marine turtles at remote locations, with a focus on the flatback turtle (Natator depressus) in the Pilbara region of Western Australia. Aerial surveys were conducted between 29 November and 6 December 2016 to overlap with the peak nesting season for flatback turtles and collected imagery was used to examine marine turtle distribution, abundance, and cumulative exposure to industrial activity relative to overlap with protected areas. Two observers independently reviewed aerial georeferenced photographs of 644 beaches and recorded turtle tracks and other evidence of turtle nesting activity. A total of 375 beaches showed signs of nesting activity by either flatback, green (Chelonia mydas) or hawksbill (Eretmochelys imbricata) turtles. Most of these beaches (85.3%) were located on islands, and the rest (14.7%) on the mainland. Half (n = 174) of the active beaches showed evidence of fresh (0–36 h. old) flatback nesting activity, with track abundance varying from 1.0 to 222.0 tracks·night−1. Six rookeries accounted for 62% of the Pilbara flatback stock. Remarkably, 77% of identified flatback rookeries occurred within protected areas. However, one-third (34%) of those were also located within 5 km of a major industrial site, including eight of the highest abundance beaches (50–250 tracks·night−1). Several key rookeries were also identified as being relatively unexposed to industry-related pressures but currently unprotected, highlighting the need for a cumulative impact assessment to be completed for this flatback stock. Finally, our aerial tallies and multiple ground-survey flatback track tallies were highly correlated and together with low intra- and inter-observer errors suggested that reliable data can be collected via aerial photogrammetry for nesting marine turtles. Such large-scale digitized surveys can therefore be used to assess the cumulative exposure of marine turtles to pressures, and to reveal new conservation opportunities.